Flora das cangas da Serra dos Carajás, Pará, Brasil: Urticaceae - Gaglioti, André Luiz; Almeida-scabbia, Renata Jimenez De; Romaniuc-neto, Sergio (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2016)
Abstract This study encompasses the species of Urticaceae registered for the cangas of Serra dos Carajás, Pará state, bringing detailed descriptions, illustrations and morphological comments of the species. Five genera and seven species of Urticaceae for the study area were found.

Resumo Este estudo engloba as espécies de Urticaceae registradas nas vegetações de cangas da Serra dos Carajás, Pará, trazendo descrições detalhadas, ilustrações e comentários morfológicos das espécies. Foram encontrados cinco gêneros e sete espécies de Urticaceae para a área de estudo.
Flora of the cangas of the Serra dos Carajás, Pará, Brazil: Urticaceae
Keywords: Cecropieae; conservation; FLONA Carajás; taxonomy; Urticeae; Cecropieae; conservação; FLONA Carajás; taxonomia; Urticeae